2010
DOI: 10.1039/c0cc00083c
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and supramolecular properties of main chain and cyclic click oligotriazoles and polytriazoles

Abstract: This Feature Article gives a summary on the conformational and supramolecular properties of a special type of click molecules, namely, main chain and cyclic oligo- and polytriazoles. The triazole ring is an interesting structural motif since it is a hydrogen bond donor and acceptor, a large molecular dipole and also a metal ligand. It can interact with a wide variety of functionalities, e.g. hydrogen bonding partners (e.g. amides or anions), molecular dipoles, and metal ions to generate many fascinating confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 115 publications
0
32
0
Order By: Relevance
“…3 The 1,2,3-triazole linkage has been revealed to be a promising amide bond surrogate, particularly with respect to its structure and hydrogen-bonding ability, while it shows a higher chemical and biological stability in comparison with the amide bonds. 4 Thus, it is now of great interest to elucidate the effects of replacement of an amide bond with a 1,2,3-triazole ring on the secondary structure as well as on the bioactivities in a wide range of amides.…”
Section: New Approach To Oligotriazoles Using a Cobalt Complex Of Promentioning
confidence: 99%
See 3 more Smart Citations
“…3 The 1,2,3-triazole linkage has been revealed to be a promising amide bond surrogate, particularly with respect to its structure and hydrogen-bonding ability, while it shows a higher chemical and biological stability in comparison with the amide bonds. 4 Thus, it is now of great interest to elucidate the effects of replacement of an amide bond with a 1,2,3-triazole ring on the secondary structure as well as on the bioactivities in a wide range of amides.…”
Section: New Approach To Oligotriazoles Using a Cobalt Complex Of Promentioning
confidence: 99%
“…4 Thus, it is now of great interest to elucidate the effects of replacement of an amide bond with a 1,2,3-triazole ring on the secondary structure as well as on the bioactivities in a wide range of amides. Recently, Angelo and Arora introduced a new class of oligotriazole as a peptidomimetic, named tirazolamer, in which the triazole rings and the sp 3 -hybridized carbons possessing amino acid side chains are alternately connected. They indicated that optically active trimeric and tetrameric triazolamers adopt zigzag conformations and show a potential inhibitory activity of HIV-1 protease.…”
Section: New Approach To Oligotriazoles Using a Cobalt Complex Of Promentioning
confidence: 99%
See 2 more Smart Citations
“…Triazole heterocycle represents non-interfering linker simply formed via so called "click" reaction -Huisgen's 1,3-diploar cycloaddition allowing for connection of independent molecular species together with accompanying interesting conformational and supramolecular features. [11][12][13] At present time only a few porphyrin dimers with 1,2,3-triazole bridge have been synthesized [14][15][16] thus the construction of "click"-connected multiporphyrin systems and particularly "click"-built porphyrin star is of special interest.…”
Section: Introductionmentioning
confidence: 99%